Evolução neurológica e eletrencefalográfica em crianças após meningencefalites purulentas - Montelli, T. B.; Ribeiro, M. V. M.; Ribeiro, R. M.; Ribeiro, M. C. L. (FapUNIFESP (SciELO), 1978)
Twenty children with diagnosed meningitis were available for prospective study; each was submitted to neurological and electroencephalographic examination, Distractability Quotient (Gesell) and Intelligence Quotient (Raven) tests. Patients were followed from 6 months to 3 years after the acute phase of the disease. There is a statistically significant difference between the D.Q of post-meningitic children and the D.Q. of non meningitic controls of the same social class and ages, when the onset of illness was before 30 months of age. No statistically significant correlation was found between the D.Q. and the patient's length of hospitalization or the first cerebrospinal fluid protein level. There is a possibility that significant correlation between the D.Q. and age at onset of illness may be observed by studying a larger number of patients. No statistically significant difference was found between the I.Q. of post-meningitic children and controls when the onset of illness was after age 4.
Neurological and electroencephalographic prospective study in children with bacterial meningitis
Keywords: central nervous system; diagnosis; electroencephalography; intelligence; major clinical study; meningitis; microorganism; preschool child; prevention; school child